A dynamic simulation model for possum and gorse control on a farm woodlot - Lee, M.W; Bennett, J; Taylor, R.J; Cavana, R.Y (School of Management Working Papers, 1996)
Managers of farm woodlots in New Zealand are confronted by two major problems: possums and gorse. If these remain uncontrolled then they have a severe impact on the returns from farm woodlots. This paper presents a system dynamics model which has been developed to assist in the analysis of control measures for managing gorse and possums on a farm woodlot in the Makara Valley, Wellington. The model has four main sectors: a tree growth module for radiata pine; a growth module for gorse; a module for the stock of possums present in the habitat; and a module of financial indicators. A number of control experiments are presented which indicate the long term financial and physical consequences of different gorse and possum control measures. The model clearly demonstrates the complex nature of the dynamic behaviour of a system involving biological and environmental factors (ie possums, gorse and trees) and human intervention (in terms of silviculture, and possum and gorse control).